Penggunaan obat anti-inflamasi nonsteroid pada anak - Fajriani Fajriani (DiscoverSys Inc., 2008)
We know that non-steroid anti-inflammatory drugs (NSAID) have analgetic, antipirettanand anti-inflammatory effect. This drugs can decrease pain simptomaticly, the most widelyprescribed drugs worldwide and being the drugs of first choice other inflammatory pain.There is many kind NSAID that we knaw, like aspirin, parasetamol, ibuprofen, mefenamicacid, endometasin, diklofenak, piroksikan and nemosulide. Every kind of NSAID has itsadvantage and dis advantage for that beneficial actions and side effects. That beneficialactions and harmful side effects of NSAID can be associated with its mechanism of action.Using NSAID for children must in attention. This article is expented to give informationand to help the collegnes in the selecting drugs NSAID for child.